PELATIHAN PEAR–DECK SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI SMP PGRI 8 SIDOARJO - Eka Nurmala Sari Agustina; Sugiantoro Sugiantoro (STKIP PGRI Sidoarjo, 2021)
This activity is a form of service that aims to improve teacher skills in developing or preparing interactive and fun learning media for students by utilizing the Pear–Deck application. This activity is carried out so that teachers are able to carry out learning both online and offline but still make students enthusiastic about participating in learning in the current situation due to COVID-19. The activities carried out are in the form of training and mentoring on the use of the Pear–Deck, combined with power points that are used during synchronous online or offline learning. The stages of the activity are the delivery of material, questions and answers, practice of making, and practice in the classroom by the teacher. This activity has a positive impact, namely that the teacher's skills in making interactive media increase and the teacher is able to apply interactive learning assisted by the Pear–Deck well.